MENINGKATKAN MINAT BACA MELALUI PROGRAM LITERASI TERSTRUKTUR PADA MATA PELAJARAN PAI DI SEKOLAH DASAR - hayati, salmi; Fitriyani (QATHRUNÂ, 2024)
The aim of this research is to increase the expected interest in reading for school students, especially religious literacy. To increase students' interest in literacy, reading habits must start from an early age and require support from various related parties, such as family, school and society. The method used in this research is descriptive qualitative with a library approach. The subjects the author used in this research were school principals and PAI teachers in elementary schools throughout Batu Bulek who had implemented the Merdeka curriculum in the classroom. Data collection techniques used were interviews, documentation, observation and literature study. As a result, PAI teachers have implemented reading literacy 10 minutes before learning begins, however, p5 is not yet very visible, and there is a lack of supporting facilities and infrastructure such as books and other tools.